Transplante xenogênico de córneas seguido de tratamento com riboflavina e radiação ultravioleta: uma alternativa promissora para doenças da córnea. - Fernanda Aparecida Silva Vieira (2025)
Keratoconus is a disease that affects the human cornea, and in severe cases, corneal transplantation is the only solution to restore vision. However, the scarcity of available corneas limits this type of treatment. Porcine cornea has emerged as an alternative due to its easy availability and low rejection rate. Following xenograft transplantation, approaches to promote collagen cross-linking in the implanted tissue have been tested. The aim of this study was to evaluate the application of riboflavin and UV radiation on decellularized lenticules implanted in rabbits through keratoplasty. The results showed that intrastromal implantation was successful, with riboflavin and UV radiation treatment yielding superior outcomes compared to implantation without these treatments. Microscopic analyses indicated that the tissue was well-adhered to, with collagen fibrils organized at the periphery and no signs of edema in the riboflavin and UV radiation-treated group. Therefore, it is concluded that the use of riboflavin and UV radiation immediately after transplantation is a promising alternative to promote corneal cross-linking.